Stripping voltammetry at mercury film plated carbon paste- and screen-printed electrodesten years of advanced laboratory practice for students at the University of Pardubice - Švancara, Ivan; Metelka, Radovan; Tesařová, Eva (Univerzita Pardubice, 2006)
In this article, a retrospective of voltammetric stripping analysis at mercury film electrodes as laboratory training for students is made, representing a reflection of the author's own research activities into their pedagogical activities. The exercise is described via its main goals and outputs, fundamental principles of measurements, conceptual structure, and methodology of the experiments. The individual aspects of the work are discussed in the light of ten year's experience from its laboratory practising at the University of Pardubice based on documentation and evaluation of a the University of Prdubice based on documentation and evaluation of a database archiving the results obtained by students over the period of 1995-2005.
Keywords: stripping voltametrie; rtuťový film; uhlíkové pastové elektrody; laboratorní cvičení; studenti